2005
DOI: 10.3732/ajb.92.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall exclusion in an eastern Amazonian forest alters soil water movement and depth of water uptake

Abstract: Deuterium-labeled water was used to study the effect of the Tapajós Throughfall Exclusion Experiment (TTEE) on soil moisture movement and on depth of water uptake by trees of Coussarea racemosa, Sclerolobium chrysophyllum, and Eschweilera pedicellata. The TTEE simulates an extended dry season in an eastern Amazonian rainforest, a plausible scenario if the El Niño phenomenon changes with climate change. The TTEE excludes 60% of the wet season throughfall from a 1-ha plot (treatment), while the control 1-ha plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 47 publications
7
83
2
1
Order By: Relevance
“…This suggests that the main water source for P. orientalis was at lower soil depths after long periods without rain. This is similar to the findings of Romero-Saltos et al (2005). Roots utilized water in the upper soil layers that was recharged by the earlier rainfall (Fig.…”
Section: Seasonal Isotopic Variations In Plant Watersupporting
confidence: 88%
“…This suggests that the main water source for P. orientalis was at lower soil depths after long periods without rain. This is similar to the findings of Romero-Saltos et al (2005). Roots utilized water in the upper soil layers that was recharged by the earlier rainfall (Fig.…”
Section: Seasonal Isotopic Variations In Plant Watersupporting
confidence: 88%
“…Lee et al (2005) showed that the inclusion of this process improved the simulation of climate over the Amazon in CLM coupled to the Community Atmosphere Model. However, Romero-Saltos et al (2005) observed that water moved upward during dry periods in the Amazon through the soil rather than through the roots. The impacts of land-atmosphere feedbacks and deep root distributions should be explored further using variable soil depth in LSMs.…”
Section: Discussionmentioning
confidence: 98%
“…In water-limited environments, where evaporative demand exceeds precipitation and water tends to be unavailable in upper soil horizons, plants are likely to have deep roots and extract water from deep soil layers (or groundwater) (Lilley and Fukai 1994;Sekiya and Yano 2002;Romero-Saltos et al 2005;West et al 2008). Actually, many perennial plants in arid and semiarid zones, as well as in seasonally dry regions, have a dimorphic root system: a network of branched surface roots potentially takes up water from upper soil layers, while deeper roots extract water stored deep in the soil that has been recharged from antecedent precipitation (Williams and Ehleringer 2000;Kulmatiski et al 2006).…”
mentioning
confidence: 99%